Ambulatory continuous peripheral nerve blocks to treat postamputation phantom limb pain: a multicenter, randomized, quadruple-masked, placebo-controlled clinical trial. Issue 3 (March 2021) - Ilfeld, Brian M.; Khatibi, Bahareh; Maheshwari, Kamal; Madison, Sarah J.; Esa, Wael Ali Sakr; Mariano, Edward R.; Kent, Michael L.; Hanling, Steven; Sessler, Daniel I.; Eisenach, James C.; Cohen, Steven P.; Mascha, Edward J.; et al.
Abstract : Phantom limb pain is thought to be sustained by reentrant neural pathways, which provoke dysfunctional reorganization in the somatosensory cortex. We hypothesized that disrupting reentrant pathways with a 6-day-long continuous peripheral nerve block reduces phantom pain 4 weeks after treatment. We enrolled patients who had an upper- or lower-limb amputation and established phantom pain. Each was randomized to receive a 6-day perineural infusion of either ropivacaine or normal saline. The primary outcome was the average phantom pain severity as measured with a Numeric Rating Scale (0-10) at 4 weeks, after which an optional crossover treatment was offered within the following 0 to 12 weeks. Pretreatment pain scores were similar in both groups, with a median (interquartile range) of 5.0 (4.0, 7.0) for each. After 4 weeks, average phantom limb pain intensity was a mean (SD) of 3.0 (2.9) in patients given local anesthetic vs 4.5 (2.6) in those given placebo (difference [95% confidence interval] 1.3 [0.4, 2.2], P = 0.003). Patients given local anesthetic had improved global impression of change and less pain-induced physical and emotional dysfunction, but did not differ on depression scores. For subjects who received only the first infusion (no self-selected crossover), the median decrease in phantom limb pain at 6 months for treated subjects was 3.0 (0, 5.0) vs 1.5 (0, 5.0) for the placebo group; there seemed to be little residual benefit at 12 months. We conclude that a 6-day continuous peripheral nerve block reduces phantom limb pain as well as physical and emotional dysfunction for at least 1 month. Abstract : Supplemental Digital Content is Available in the Text.A 6-day ambulatory continuous peripheral nerve block reduces phantom limb pain and pain-induced physical and emotional dysfunction for at least 4 weeks after treatment.